Financial Literacy, Financial Technology (FinTech), and Locus of Control on Financial Management Behavior - Riri Novianti; Nora Ria Retnasih (Ekonomis: Journal of Economics and Business, 2023)
This study aims to analyze how financial literacy, FinTech, and also locus of control influence the financial management behavior of Faculty of Economics (FE) at UIN Malang students. This study uses descriptive quantitative methods with primary data questionnaires. The population of this study was 1,520 students of FE UIN Malang. The sample used was 317 students calculated using the slovin formula. The data analysis used was multiple linear regression with SPSS 25. The results showed that financial literacy and locus of control significantly affected financial management behavior. While FinTech has no significant effect on financial management. In addition, financial literacy, FinTech, and locus of control simultaneously influence financial management behavior.